Large‐scale separation of antipsychotic alkaloids from Rauwolfia tetraphylla L. by pH‐zone‐refining fast centrifugal partition chromatography1. Issue 2 (29th November 2012) - Maurya, Anupam; Gupta, Shikha; Srivastava, Santosh K.
<x xml:space="preserve">Abstract</x> pH‐zone‐refining centrifugal partition chromatography was successively applied in the large‐scale separation of close Rf antipsychotic indole alkaloids directly from CHCl3 fraction of Rauwolfia tetraphylla leaves. Two experiments with increasing mass from 500 mg to 3 g of crude alkaloid extracts (1C) of R. tetraphylla were carried out in normal‐displacement mode using a two‐phase solvent system composed of methyl tert‐butyl ether/ACN/water (4:1:5, v/v/v) where HCl (12 mM) was added to the lower aqueous stationary phase as a retainer and triethylamine (5 mM) to the organic mobile phase as an eluter. The two centrifugal partition chromatography separations afforded a total of 162.6 mg of 10‐methoxytetrahydroalstonine (1) and 296.5 mg of isoreserpiline (2) in 97% and 95.5% purity, respectively, along with a 400.9 mg mixture of α‐yohimbine and reserpiline (3 and 4). Further, this mixture was resolved over medium pressure LC using TLC grade silica gel H (average particle size 10 μm), which afforded 160.4 mg of α‐yohimbine (3) and 150.2 mg of reserpiline (4) in >95% purities. The purity of the isolated antipsychotic alkaloids was analyzed by high‐performance LC and their structures were characterized on the basis of their 1D, 2D NMR and electrospray ionization‐mass spectroscopic data.